The Implementation of Snowball Throwing Strategy to Develop Students Ability in Reading Comprehension Social Function of Descriptive Text - Fadilah, Nadiatul; Gaffar, Muhammad Andriana (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
This study aims to analyze the implementation of the Snowball Throwing strategy to develop students’ ability in Reading Comprehension social function of descriptive text and to analyze students’ responses the implementing of Snowball Throwing strategy to develop students’ ability in Reading Comprehension of descriptive text. This study used a qualitative research method based on Classroom Action Research. The writer uses observation, field notes, and interviews as instruments. The participants in this study were 20 students of class X MIPA 3 MA ASSHIDDIQIYAH 3 Karawang. Research data in cycle 1 shows that the snowball-throwing strategy encourages students to understand reading descriptive texts. Students can perform better reading skills. This data is supported by interviews with student data showing positive responses in teaching reading using the snowball throwing strategy. In cycle 2, it showed increased student participation when conducting discussions; students seemed to enjoy and enjoy the teaching and learning process more. This data is supported by student responses which say that students like learning to do reading comprehension using the snowball-throwing strategy. Based on the study’s results, the snowball-throwing strategy can encourage students to understand descriptive texts and make them actively participate in learning to read.